تقييم سريري وشعاعي للشفاء بعد تطبيق الـ MTA على الانثقابات الميكانيكية لمفترق الجذور في الأرحاء المؤقتة - نور الله عبد الوهاب; بدر فائق; الدايري براءه (Latakia University Journal -Medical Sciences Series, 2019)
Aim: The aim of this study is to evaluate the clinical and radiographic healing after repairing mechanical furcal perforations that occurred in primary molars by using MTA (Mineral Trioxide Aggregate). Materials & Methods: 34 primary molars in 32 children aged 5-10 years were treated by using MTA material after the occurrence of furcal perforation during pulpotomy procedure. Cases had been followed clinically and radiographically within 12 months. Statistical analyses were performed at p-value =0.05. Results: All teeth were asymptomatic at the first week. Overall success rate was 79.3%. There was significant statistically difference between overall- success and failure rates (p-value=0.002), but there was no significant differences between overall- success rates according to the age, time of the treatment, perforation size, bleeding (p-value > 0.05). Conclusions: Iatrogenic furcal perforations that may occur during pulpotomy in primary molars can be treated successfully by using MTA, and the immediate management of the small sized- perforations may have the best prognosis for treatment. الهدف: تهدف هذه الدراسة إلى تقييم الشفاء السريري والشعاعي بعد إصلاح الانثقابات الميكانيكية لمفترق الجذور في الأرحاء المؤقتة الحاصلة أثناء المعالجة بطريقة بتر اللب باستخدام مادة الـ MTA (Mineral Trioxide Aggregate) (تجمع الأكاسيد الثلاثي). المواد والطرائق: كان لدينا 34 رحى مؤقتة لـ 32 طفلاً بأعمار 5-10 سنوات تمت معالجتهم باستخدام الـ MTA بعد حدوث انثقاب المفترق أثناء المعالجة ببتر اللب. وتمت متابعة الحالات سريرياً وشعاعياً خلال 12 شهراً, ثم أجريت التحاليل الإحصائية عند مستوى دلالة p-value=0.05. النتائج: كانت جميع الأسنان غير عرضية خلال الأسبوع الأول, وسجل معدل النجاح الكلي 79.3%خلال الـ 12 شهراً, كان لدينا فرق هام إحصائياً بين معدلي النجاح والفشل الكلييين (p-value=0.002), ولم يكن هناك فرق هام إحصائياً بين معدلات النجاح الكلية تبعاً للعمر أو وقت المعالجة أو حجم الانثقاب أو النزف (p-value > 0.05). الخلاصة: يمكن أن تعالج انثقابات المفترق رضية المنشأ في الأرحاء المؤقتة المعالجة ببتر اللب باستخدام الـ MTA بنجاح, وقد يكون التدبير المباشرة للانثقابات صغيرة الحجم الإنذار الأفضل للمعالجة.